PERAN FUKUN DALAM KAMPANYE PEMILU: ALTERNATIF TERHADAP MEDIA MASSA DAN MEDIA BARU - Herman Seran (Universitas Mercu Buana, 2019)
This study aims to reveal the communication media used in conducting legislative elections in 2019, especially in rural areas. Several studies have shown that the presence of mass media such as television and radio, as well as the presence of new media (new media) through social media platforms and other online media have contributed to support the activities of the election campaign. However, in the technological development of communication media, in a rural area there is a channel / other communication media were also very successful as a campaign activity. This study specifically examines the communication media used by legislative candidates in campaign activities in rural areas. In the legislative election campaign in 2019 in rural areas Beskem (pseudonym), fukun be an alternative to the media in the campaign due to limited public access to the mass media and new media. Fukun became a communicator as well as a medium for legislative candidates to meet with village communities. In addition, fukun can mobilize the masses in election campaign activities.